IMPLEMENTATION OF TRANSFORMATIONAL LEADERSHIP MODEL IN ISLAMIC EDUCATION - Arrosyid, Moh. Kholil; Chotib, Moch.; Anwar, Moh. (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Islamic education is one of the main pillars in the development of individual character and knowledge based on religious values, especially in this case the application of the transformational leadership model in Islamic education. The purpose of this study is to determine how the implementation of the transformational leadership model in Islamic education at the Miftahul Ulum Bengkak Wongsorejo Banyuwangi Islamic Boarding School Foundation. The method used in this study uses a descriptive qualitative research method, with informants as the heads of the Foundation and the administrators of the education sector. The results of this study indicate that the implementation of the transformational leadership model at the Miftahul Ulum Bengkak Wongsorejo Banyuwangi Islamic Boarding School Foundation involves establishing an inspiring vision, open communication, and empowering staff. The head of the foundation and the education administrators are active in disseminating the vision, encouraging constructive dialogue, and providing support and training to improve staff skills. The impact of this practice is very positive: the motivation of teaching staff increases, which leads to better performance, while students experience increased enthusiasm for learning and academic achievement. The evaluation shows that this strategy is effective, although there are obstacles such as limited resources that are being addressed by adjusting the strategy and increasing support.